Swelling, Thermal and Mechanical Characterizations of High-Density Polyethylene/ Recycled Biochar Composites - Sameer AWAD (Turkish Chemical Society, 2021)
This article aims to study recycled biochar (R-BCH) improvements on the high-density polyethylene (HDPE) matrix properties. A series of composites was developed with a different loading varying from 0 to 10 wt.% of R-BCH, using a twin-screw extruder followed by compression molding. The results were showed that the addition of 3-10% of R-BCH in pure HDPE led to an increase in the tensile strength, modulus of elasticity, and a decrease of elongation at break. Furthermore, the differential scanning calorimetry analysis (DSC) results showed that incorporating R-BCH into pure HDPE improved thermal properties because interfaces between R-BCH and pure HDPE caused decreased brittle behaviour and enhanced the high crosslinking of pure HDPE.